You are on page 1of 15

1

x2 + y2 = 1

(1)

x = cos(t)

y = sin(t)
x, y
t
2
x2 y2 = 1

(2)

x = sec(t)

y = tan(t)

t 1
t
t
t
t

1
A = r2 t
2

(3)

r = 1
t = 2A
1

(4)

t x

t
x
x2 y2 = 1 P(h, k) P
x M

h
t
1
= hk
x2 1 dx
2 2
1
(
)]h

1[
1 2
= h h 1 x x2 1 ln x + x2 1
1
2
2
(
)

1
= ln h + h2 1
2
OPM

(
)

t = ln h + h2 1

t
(
)

t = ln h + h2 1

et = h + h2 1 e

et h = h2 1
e2t 2het + h2 = h2 1
e2t + 1 = 2het
h=

et + et
2

2et

(h, k) h2 k2 = 1
k 2 = h2 1
e2t + 2 + e2t
1
4
e2t 2 + e2t
=
4

k=

et et
2

(h, k) x, y

et + et

x
=

et

y=
2

(5)

(6)

cos(t) sin(t)

hyperbolic function

cos(t) sin(t) hyperbolic sinehyperbolic cosine 2


sin , cos h
ex ex
2
ex + ex
cosh(x) =
2
sinh(x) =

sinh(x) ex ex e2x 1
=
=
cosh(x) ex + ex e2x + 1
cosh(x) ex + ex e2x + 1
coth(x) =
=
=
sinh(x) ex ex e2x 1
1
2
sech(x) =
= x
cosh(x) e + ex
1
2
csch(x) =
= x
sinh(x) e ex

tanh(x) =

sinh(x)
ex ex
ex ex
sinh(x) =
=
= sinh(x) cosh(x)
2
2

2 sine

sincosine cos

1.1
x = cos(t), y = sin(t) x2 + y2 = 1
cos2 (t) + sin2 (t) = 1
cos2 (t)
1 + tan2 (t) = sec2 (t)
sin2 (t)
cot2 (t) + 1 = csc2 (t)

x = cosh(t), y = sinh(t) x2 y2 = 1
cosh2 (t) sinh2 (t) = 1
cosh2 (t)
1 tanh2 (t) = sech2 (t)
sinh2 (t)
coth2 (t) 1 = csch2 (t)

sinh(x + y) = sinh(x) cosh(y) + cosh(x) sinh(y)


cosh(x + y) = cosh(x) cosh(y) + sinh(x) sinh(y)
tanh(x + y) =

tanh(x) + tan(y)
1 + tanh(x) tanh(y)

y x
sinh(2x) =2 sinh(x) cosh(x)
cosh(2x)
= cosh2 (x) + sinh2 (x)
::::::::
=2:::::::::::::
cosh2 (x) 1
=1::::::::::::
+ sinh2 (x)
tanh(2x) =

2 tanh(x)
1 + tanh2 (x)

x
x
2
( )
cosh(x) 1
x
sinh2
=
2
2
( )
cosh(x) + 1
x
cosh2
=
2
2

sin

cos2 (x) + sin2 (x) = 1


sin(x)
cosh2 (x) sinh2 (x) = 1

cos(x + y) = cos(x) cos(y) sin(x) sin(y)

sin(x) sin(y)
cosh(x + y) = cosh(x) cosh(y) + sinh(x) sinh(y)

( )
1 cos(x)
x
sin
=
2
2
2

( )
x
sin

2
( )
1 cosh(x)
2 x
=
sinh
2
2
2

eix = cos(x) + i sin(x)


ix ex
x2 ix3

+ ...
eix =1 + ix
2
3!
(
)
(
)
x2
x3
= 1
+ ... + i x
+ ...
2!
3!
= cos(x) + i sin(x)
x x
eix = cos(x) i sin(x)

eix = cos(x) + i sin(x)


eix = cos(x) i sin(x)
2 2i
eix + eix
2
ix
e eix
sin(x) =
2i

cos(x) =


eix + eix
= cosh(ix)
2
eix eix
sin(x) =
= i sinh(ix)
2i

cos(x) =

ix x
cosh(x) = cos(ix) = cos(ix)
i sinh(x) = sin(ix)

sinh(x) = i sin(ix) = i sin(ix)


sin
sin(x) sin(y) =(i sinh(ix))(i sinh(iy))
= sinh(ix) sinh(iy)
i 1 sinh
i
cosh(x + y) = cos(ix + iy)
= cos(ix) cos(iy) sin(ix) sin(iy)
= cosh(x) cosh(y) (i sinh(x))(i sinh(y))
= cosh(x) cosh(y) + sinh(x) sinh(y)
sin
De Moive
(cos(x) i sin(x))n = cos(nx) i sin(nx)

(cosh(ix) sinh(ix))n = cos(inx) sin(inx)


ix x
(cosh(x) sinh(x))n = cosh(nx) sinh(nx)

1.2

(
)
ex + ex
d
d ex ex
=
sinh(x) =
= cosh(x)
dx
dx
2
2

(
)
ex ex
d
d ex + ex
cosh(x) =
=
= sinh(x)
dx
dx
2
2
tanh(x)
d
tanh(x)
dx (
)
d sinh(x)
=
dx cosh(x)
cosh(x) cosh(x) sinh(x) sinh(x)
=

cos2 (x)
1
=
cosh2 (t) sinh2 (t) = 1
2
cos (x)
= sech2 (x)
3
d
coth(x) = csch2 (x)
dx
d
sech(x) = tanh(x) sech(x)
dx
d
csch(x) = coth(x) csch(x)
dx

1.3

y = sinh1 (x)

sinh(y) = x

x=

e y ey
2

2 e y e y
e2y 2xe y 1 = 0

e =
y

2x

= x

4x2 + 4
2

x2 + 1

y = sinh1 (x) = ln x + x2 + 1

e y = sinh(y) + cosh(y)

e y ey e y + ey
+
2
2

sinh(y) = x , cosh(x) = sinh2 (y) + 1 = x2 + 1

e y = sinh(y) + cosh(y) = x +

10

x2 + 1

y = ln x + x2 + 1

y = cosh1 (x)
e y = sinh(y) + cosh(y)

= x2 1 + x


y = ln x2 1 + x

,x 1

tanh1 (x)
x = tanh(y) =

e2y 1
e2y + 1

xe2y + x = e2y 1

e2y =

2y = ln

1+x
1x
(

1+x
1x

(
)
1
1+x
y = tanh (x) = ln
, |x| < 1
2
1x
1
tanh1 (x) coth1 (x)
x

(
)
1
1+x
1
coth (x) = ln
, |x| > 1
2 x1


2

1
1

x
1
sech (x) = ln
+
,0 < x 1

x
x


1 + x2 1
1
+
csch (x) = ln
,x , 0

|x|
x
1

tanh(x)
|y| < 1 tanh1 (x) |x| < 1

11

1.4
d
sinh1 (x)
dx

d
=
ln x + x2 + 1
dx
1 + x2
x +1
=

x + x2 + 1

x2 + 1 x

2
x2 + 1 x + x x2
x +1
=
x2 + 1 x2

x2
= x2 + 1
x2 + 1
2
2
x +1x
=
x2 + 1
1
=
1 + x2

dy
1
= dx
dx
dy
y = sinh1 (x) x = sinh(y) y
1
cosh(y)
y x

1
1 + sinh2 (y)

1
1 + x2

12

d
sinh1 (x) =
dx

1
1
1
=
=

d
cosh(y)
sinh(y)
1 + x2
dy
d
1
1
1
=
cosh1 (x) = d
=
dx
sinh(y)
cosh(y)
x2 1
dy
d
tanh1 (x) =
dx
d
coth1 (x) =
dx

d
dy

1
1
1
=
=
2
1 x2
tanh(y)
sech (y)

d
dy

1
1
1
=
=
2
1 x2
coth(y)
csch (y)

d
sech1 (x) =
dx

1
1
1
=
=

d
sech(y) tanh(y)
sech(y)
x 1 x2
dy
d
1
1
1
csch1 (x) = d
=
=
dx
csch(y) coth(y)
csch(y)
|x| 1 + x2
dy

1.5

ex ex
sinh(x) =
[ 2(
) (
) ]
1
x2 x3
x2 x3
=
1+x+
+
+ ... 1 x +

+ ...
2
2! 3!
2! 3!
(
)
1
x3
=
2x + 2 + . . .
2
3!
3
x
= x+
+ ...
3!

ex + ex
cosh(x) =
[ 2(
) (
) ]
1
x2 x3
x2 x3
=
1+x+
+
+ ... + 1 x +

+ ...
2
2! 3!
2! 3!
(
)
x2
1
2 + 2 + ...
=
2
2!
2
x
= 1+
+ ...
2!

13

sinh(x) ex cosh(x)
ex
ex = sinh(x) + cosh(x)
coth(x)

tanh1 (x)

1 x2

1
= 1 + x2 + x4 + x6 + . . .
1 x2

tanh1 (x) = C + x +

x3 x5
+
+ ...
3
5

C x = 0
tanh1 (0) = 0 = C + 0 + 0 + . . .
C = 0
sinh1 (x)

1
1 + x2

(
) 12
1
1
1
1
1
= 1 + x2
= C02 + C12 x2 + C22 x4 + C32 x6 + . . .

1 + x2

sinh1 (x) = C + C02 x + C12

1 x5
1 x6
x3
+ C22
+ C32
+ ...
3
5
6

C x = 0
sinh1 (0) = 0 = C + 0 + 0 + . . .
C = 0

14

1.6

inversive geometry

dx

1 + x2
x = tan(t), dx = sec2 (t)dt

sec2 (t)dt
= sec(t)dt
sec(t)
= ln |sec(t) + tan(t)| + C


= ln 1 + x2 + x + C
x = sinh(t), dx = cosh(t)dt

cosh(t)dt
=
dt
cosh(t)
= t + C = sinh1 (x) + C

1 + x2 dx

1
cosh(t) cosh(t)dt =
1 + cosh(2t) dt
2
[
]
sinh(2t)
1
=
t+
+C
2
2
1
= [t + sinh(t) cosh(t)] + C
2
]

1[
=
sinh(x) + x 1 + x2 + C
2

15